Managing gastrointestinal symptoms after cancer treatment: a practical approach for gastroenterologists. Issue 3 (2nd October 2012) - Muls, Ann C; Watson, Lorraine; Shaw, Clare; Andreyev, H Jervoise N
Abstract : The percentage of the population living with a diagnosis of cancer is rising. By 2030, there will be 4 million cancer survivors in the UK. One quarter of cancer survivors are left with physical symptoms, which affect their quality of life. Gastrointestinal (GI) symptoms are the most common of all chronic physical side-effects of cancer treatment and have the greatest impact on daily activity. Cancer therapies induce long-term changes in bowel function due to alterations to specific GI physiological functions. In addition, the psychological effect of a cancer diagnosis, new GI disease or pre-existing underlying conditions, may also contribute to new symptoms. Twenty-three upper GI symptoms have been identified as occurring after pelvic radiotherapy. After upper GI cancer treatment, the most troublesome symptoms include reflux, abdominal pain, indigestion, diarrhoea and fatigue. Often, several symptoms are present simultaneously and women experience more symptoms than men. The symptoms which patients rate as most difficult are urgency, wind, diarrhoea, incontinence, abdominal pain and rectal bleeding. Recent UK Guidance on managing GI symptoms suggests that these symptoms can be treated especially if gastroenterological advice is combined with dietetic and nursing input to optimise investigations and management. However, as different pathological processes can result in identical symptoms; a systematic, 'algorithmic' approach to assess and treat these symptoms is required. This paper aims to illustrate the value of such an approach to investigate and treat the most common GI symptoms that trouble patients. The algorithm allows clinicians to institute a comprehensive medical management plan.